2019
DOI: 10.9770/jesi.2019.7.1(45)
|View full text |Cite
|
Sign up to set email alerts
|

Towards to a single innovation space in the agrarian sector of the member states of the Eurasian economic union: a case study

Abstract: The article deals with the formation of a single innovation space in the agrarian sector of the member states of the Eurasian Economic Union with the aim of rational use of their total scientific potential. The approaches to the formation of a common innovative space of the EU countries are considered. A distinctive feature of the modern stage of development of the innovation space in the agro-industrial sector of the Eurasian Economic Union is the intensification of cross-border cooperation of the participati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 17 publications
0
14
0
1
Order By: Relevance
“…There was an increase in prices for bread and other products. Increase in prices for bread affected poor people greatly [48][49][50][51][52][53][54][55][56][57][58][59].…”
Section: Resultsmentioning
confidence: 99%
“…There was an increase in prices for bread and other products. Increase in prices for bread affected poor people greatly [48][49][50][51][52][53][54][55][56][57][58][59].…”
Section: Resultsmentioning
confidence: 99%
“…The authors have identified the effects of resource use optimization in the conditions of market relations transformation [42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57]:…”
Section: Resultsmentioning
confidence: 99%
“…The peculiarity of the system of state regulation of environmental activities is the presence of several levels of regulation: national, regional and local. In recent years, there has been a tendency to increase the number of government bodies, including sectoral ministries responsible for the state of the environment in their area, and to expand their functions in this area (Shaytura et al, 2018;Paptsov and Nechaev, 2019). In Russia, a unified state policy in the field of environmental protection and environmental management is carried out by the Ministry of Natural Resources and Environment of the Russian Federation (the Ministry of Natural Resources of Russia), which performs coordination functions, develops and publishes relevant regulatory legal acts and controls their implementation (Frolova et al, 2019;Magsumov, 2019a,b).…”
Section: Resultsmentioning
confidence: 99%